Helicobacter pylori type 4 secretion systems as gastroduodenal disease markers - Bui Hoang Phuc (Nature Portfolio, 2021)
Abstract Although the type 4 secretion system of the integrating and conjugative elements (tfs ICE) is common in Helicobacter pylori, its clinical association with the cag pathogenicity island (cagPAI) have not yet been well-investigated. In this study, Vietnamese patient H. pylori samples (46 duodenal ulcer (DU), 51 non-cardia gastric cancer (NCGC), 39 chronic gastritis (CG)) were fully sequenced using next-generation sequencing and assembled into contigs. tfs3, tfs4, and cagPAI genes were compared with the public database. Most (94%) H. pylori strains possessed a complete cagPAI, which was the greatest risk factor for clinical outcomes, while the prevalences of tfs3 and tfs4 were 45% and 77%, respectively. Complete tfs3 and tfs4 were found in 18.3% and 17.6% of strains, respectively. The prevalence of H. pylori strains with complete tfs3 ICE in DU patients was significantly higher than that in NCGC patients (30.4% vs 11.7%, P < 0.05). In addition, the prevalence of strains with complete tfs3 ICE and cagPAI was significantly higher in DU patients than that in NCGC (28.4% vs 9.8%, P = 0.038) and CG patients (28.2% vs 7.7%, P = 0.024). cagPAI and complete tfs3 increased the risk of DU compared to NCGC (OR = 3.56, 95%CI: 1.1–14.1, P = 0.038) and CG (OR = 4.64, 95%CI: 1.1–27.6, P = 0.024). A complete cluster of tfs3 ICE was associated with gastroduodenal diseases in Vietnam. However, there was a low prevalence of the dupA/complete dupA cluster (15.4%) in the Vietnam strains. The prevalence of cagPAI in Vietnam strains was significantly higher than in US (P = 0.01) and Indonesia (P < 0.0001); the prevalence of the dupA cluster was also higher in the Vietnam strains than in the Indonesian strains (P < 0.05). In addition, the prevalence of ctkA, an accessory gene of tfs3, was significantly different between Vietnam and US strains (28% vs 2%, P = 0.0002). In summary, the acquisition of tfs3/4 ICE was common in H. pylori strains in patients with gastroduodenal disease in Vietnam, and the complete cluster of tfs3 ICE was a reliable marker for the severity of disease in the H. pylori infected population.